Shedding light on the entropy change found for the transition stage II→stage I of Li-Ion storage in graphite - Leiva, Ezequiel Pedro M. (2016)
In order to examine the controversial hypothesis put forward to explain the entropy step experimentally observed for the stage II to stage I transition for lithium intercalation in graphite, a transparent statistical mechanical model is developed. The results obtained show that the entropy increase can be explained by the change of configurational entropy occurring at occupation of half of the lattice. Comparison with experimental data shows that attractive interactions between intercalated particles in the same layer must be assumed, in agreement with the ansatz made in the original experimental work.